Executive and legislative authority in the administration of local government based on the principles of good governance - Wijatono, Setia; Hasanah, Siti; Jiwantara, Firzhal Arzhi (Institute Of computer Science (IOCS), 2025)
The implementation of local government in the application of Good Governance principles is a demand from the community to the government, One of the forms of good governance is the image of democratic governance.The purpose of this study is to explain and analyze the authority of the Regional Government and the Regional Representative Council in realizing good governance. This study uses a normative juridical methodwith a statute approachand a conceptual approachin a qualitative descriptive analysis, the data used in this study is sourced from primary legal materials, secondary legal materials and library research results from various references.The results of the study show that in carrying out their duties and functions, even though the position is parallel between the Regional Government and the DPRD. Supervision continues to run as the DPRD's duty always supervises both the government in running the wheels of government and including supervision in public services andlocal governments must not act by abusing authority and exceeding authority, or without authority, so as to realize the state goals (local governments) of welfare in order to implement the principles of good governance.